JP6348317B2 - Decomposable adhesive composition - Google Patents
Decomposable adhesive composition Download PDFInfo
- Publication number
- JP6348317B2 JP6348317B2 JP2014076467A JP2014076467A JP6348317B2 JP 6348317 B2 JP6348317 B2 JP 6348317B2 JP 2014076467 A JP2014076467 A JP 2014076467A JP 2014076467 A JP2014076467 A JP 2014076467A JP 6348317 B2 JP6348317 B2 JP 6348317B2
- Authority
- JP
- Japan
- Prior art keywords
- adhesive
- ion
- heating
- adhesive composition
- strength
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Expired - Fee Related
Links
Landscapes
- Adhesives Or Adhesive Processes (AREA)
Description
本発明は、接着剤によって組み立てられた構造体又は物品をその接着接合部において容易に解体させることを可能にする解体性接着剤に関する。 The present invention relates to a dismantling adhesive that allows a structure or article assembled with an adhesive to be easily disassembled at its adhesive joint.
接着剤は、構造用接着剤をはじめとして、より接着力が強く、より耐久性が長く、さらには、耐熱性、温度環境の変動にも強いものが求められ、開発が進められてきた。しかしながら、限り有る資源を有効に使用しようとするリサイクルの面では、アセンブリーされた部品を再利用するために、解体可能な接着剤の開発が必須である。解体性接着剤とは、使用期間後に何らかの処置により接合部をはがしうるものである。このような接着剤として、熱可塑性接着剤は、加熱により接合部の解体が可能であるが、いったん冷却すると再び接着力が復元する。解体する場合は、接着剤だけを加熱することは困難であるため、高い雰囲気温度下で解体する必要があるが、高温となった接合物の解体は、危険性の高いものであった。 Adhesives, including structural adhesives, are required to have stronger adhesive strength, longer durability, and more resistant to heat resistance and temperature fluctuations, and have been developed. However, in terms of recycling in order to effectively use limited resources, it is essential to develop an adhesive that can be disassembled in order to reuse the assembled parts. A decomposable adhesive can be peeled off by some treatment after a period of use. As such an adhesive, the thermoplastic adhesive can be disassembled by heating, but once cooled, the adhesive strength is restored again. When disassembling, since it is difficult to heat only the adhesive, it is necessary to disassemble at a high atmospheric temperature. However, disassembling a bonded product that has reached a high temperature is highly dangerous.
この問題を解決するため、熱可塑性よりもより高強度の接着力が要求される熱硬化性接着剤にも適用可能な解体性接着剤として、接着剤成分にバーミキュライトや熱膨張性黒鉛等の熱膨張性無機物を添加した解体性接着剤の開発が進められている。しかしながら、これらの解体性接着剤は、加熱後に接着強度が低下するものの完全に強度がゼロにはならないという問題があった(特許文献1参照)。また、解体温度は400℃以上という高温を想定しているため、多大な熱エネルギーが必要であることに加え、被着体が樹脂材料の場合、加熱時に被着体自身が熱劣化するため再利用が困難であるという問題があった(特許文献2参照)。 In order to solve this problem, as a decomposable adhesive that can be applied to thermosetting adhesives that require higher strength than thermoplasticity, the adhesive component can be made of heat such as vermiculite or thermally expandable graphite. Development of a dismantling adhesive to which an expansive inorganic substance is added is in progress. However, these decomposable adhesives have a problem that the strength does not completely become zero although the adhesive strength decreases after heating (see Patent Document 1). In addition, since the disassembly temperature is assumed to be 400 ° C. or higher, a large amount of heat energy is required. In addition, when the adherend is a resin material, the adherend itself is thermally deteriorated during heating. There was a problem that utilization was difficult (refer patent document 2).
接着剤成分に熱膨張性樹脂バルーンや化学発泡剤を添加した解体性接着剤の開発も進められている。しかしながら、これらの解体性接着剤は、高強度の接着剤は解体できず、10MPa以下の接着強度を有する接着剤の解体に留まっていた(特許文献3、特許文献4参照)。 Development of a decomposable adhesive in which a heat-expandable resin balloon or a chemical foaming agent is added to the adhesive component is also underway. However, these dismantling adhesives cannot dismantle high-strength adhesives, and have only been dismantling adhesives having an adhesive strength of 10 MPa or less (see Patent Documents 3 and 4).
高接着強度を有する接着剤を解体するため、接着剤成分に有機ポリマーを添加した解体性接着剤の開発が進められているが、200℃以上という高温条件下でのみ接着強度がゼロとなるため、熱可塑性接着剤同様に、高温となった接合物の解体は、危険性が高いという問題があった(特許文献5参照)。 In order to dismantle adhesives with high adhesive strength, the development of decomposable adhesives in which an organic polymer is added to the adhesive component is underway, but the adhesive strength becomes zero only under high temperature conditions of 200 ° C or higher. As with the thermoplastic adhesive, there is a problem that the disassembly of the bonded product that has reached a high temperature has a high risk (see Patent Document 5).
また、熱硬化性接着剤に適用可能な酸化剤混入接着剤の開発も進められているものの、一部では酸化剤と硬化剤の反応により発泡し、初期強度が低下してしまうという問題があった(特許文献6参照)。この問題を回避するために、接着剤との混合前に、酸化性陰イオンを含有するオニウム塩とアミン系化合物とを反応させる方法が検討されているが、接着剤製造工程を増やす必要があった(特許文献7参照)。 Although development of oxidant-mixed adhesives that can be applied to thermosetting adhesives has also been promoted, there is a problem that in some cases, foaming is caused by the reaction between the oxidant and the curing agent, and the initial strength is lowered. (See Patent Document 6). In order to avoid this problem, a method of reacting an onium salt containing an oxidizing anion with an amine compound before mixing with the adhesive has been studied. However, it is necessary to increase the number of steps for manufacturing the adhesive. (See Patent Document 7).
さらに、有機カチオンのハロゲン化物を添加した解体性接着剤の開発も進められているが、一部では潮解性が高いために接着剤製造時、及び接着剤塗布、貼り付け時に大がかりな調湿設備や窒素雰囲気下での作業が必要であった(特許文献8参照)。 In addition, demolition adhesives with added organic cation halides are being developed, but due to high deliquescence in some areas, large-scale humidity control equipment is required during adhesive production, adhesive application, and pasting And work in a nitrogen atmosphere was necessary (see Patent Document 8).
本発明が解決しようとする課題は、簡便な製造方法により、高強度の接着剤を用いて接合された構造体又は物品を、必要な場合に外的刺激によって、比較的低温で接着接合部を解体可能な接着剤組成物を提供することである。 The problem to be solved by the present invention is that a structure or article bonded using a high-strength adhesive by a simple manufacturing method can be used to form an adhesive bonded part at a relatively low temperature by external stimulation when necessary. It is to provide a decomposable adhesive composition.
本発明者は、上記課題を解決すべく鋭意研究し実験を重ねた結果、ハロゲン化無機オニウム化合物を有機系接着剤成分に含有してなる加熱解体性接着剤組成物が、上記課題を解決できることを見出し、本発明を完成するに到った。
すなわち、本発明は以下のとおりのものである。
[1](A)有機系接着剤成分、及び(B)無機オニウムイオンとハロゲンイオンとの化合物を含む加熱解体性接着剤組成物。
As a result of intensive studies and experiments to solve the above-mentioned problems, the present inventor is able to solve the above-mentioned problems by a heat- disintegratable adhesive composition containing a halogenated inorganic onium compound in an organic adhesive component. As a result, the present invention has been completed.
That is, the present invention is as follows.
[1] A heat decomposable adhesive composition comprising (A) an organic adhesive component, and (B) a compound of an inorganic onium ion and a halogen ion.
[2]前記無機オニウムイオンが窒素の水素化物である、前記[1]に記載の加熱解体性接着剤組成物。 [2] The heat decomposable adhesive composition according to [1], wherein the inorganic onium ion is a hydride of nitrogen.
[3]前記窒素の水素化物がアンモニウムイオンである、前記[2]に記載の加熱解体性接着剤組成物。 [3] The heat decomposable adhesive composition according to [2], wherein the nitrogen hydride is an ammonium ion.
[4]前記ハロゲンイオンがヨウ化物イオンである、前記[1]〜[3]のいずれかに記載の加熱解体性接着剤組成物。 [4] The heat decomposable adhesive composition according to any one of [1] to [3], wherein the halogen ion is iodide ion.
[5]前記(A)有機系接着剤成分がエポキシ樹脂系接着剤である、前記[1]〜[4]のいずれかに記載の加熱解体性接着剤組成物。 [5] The heat decomposable adhesive composition according to any one of [1] to [4], wherein the (A) organic adhesive component is an epoxy resin adhesive.
本発明によれば、無機オニウムイオンとハロゲンイオンとの化合物は、有機系接着剤との反応性もなく、潮解性もないため、高強度の接着剤を用いて接合された構造体又は物品を、必要な場合に外的刺激によって、比較的低温で接着接合部を解体可能な接着剤を簡便に提供することが可能となる。 According to the present invention, the compound of inorganic onium ions and halogen ions is not reactive with organic adhesives and does not have deliquescence. Therefore, a structure or article bonded using a high-strength adhesive is used. When necessary, it is possible to easily provide an adhesive capable of disassembling the adhesive joint at a relatively low temperature by external stimulation.
以下、本発明の好ましい実施態様を詳細に説明する。
本発明において利用できる有機系接着剤成分としては、何ら限定されるものではないが、本発明の主旨が、解体しにくいものを解体することにあるから、構造用の接着剤を用いること好ましい。構造用接着剤とは、「長期間破壊することなく、その最大破壊荷重に比較的近い応力を加えることのできる信頼性の保証された接着剤」(接着応用技術 日経技術図書株式会社発行 1991年 P93 接着剤の分類参照)であり、化学組成による分類によれば、(同上図書 P99)熱硬化性、アロイがよい。
Hereinafter, preferred embodiments of the present invention will be described in detail.
The organic adhesive component that can be used in the present invention is not limited in any way. However, since the gist of the present invention is to dismantle one that is difficult to disassemble, it is preferable to use a structural adhesive. A structural adhesive is "a reliable adhesive that can apply a stress that is relatively close to its maximum breaking load without breaking for a long period of time" (adhesive application technology, Nikkei Technical Library Co., Ltd., 1991) According to the classification by chemical composition (see book P99), thermosetting and alloy are good.
本発明の解体性接着剤に用いることができる接着剤成分を例示すれば、酢酸ビニル樹脂、ポリアミド樹脂、ポリウレタン樹脂、ポリエステル樹脂、ユリア樹脂、メラミン樹脂、レゾルシノール樹脂、フェノール樹脂、エポキシ樹脂、ポリイミド樹脂、ポリベンズイミダゾール、アクリル(SGA)、アクリル酸ジエステル、シリコーンゴム系などを主成分とする接着剤を挙げることができる。アロイとしては、エポキシフェノリック、エポキシポリサルファイド、エポキシナイロン、二トリルフェノリック、クロロプレンフェノリックビニルフェノリック等、または上記物質を変性させた樹脂、上記物質を2種類以上混合した樹脂が使用できる。特に、エポキシ樹脂系接着剤は、副生成物を遊離せずに硬化し、高い剪断強さを有しており、好ましい。 Examples of adhesive components that can be used in the dismantling adhesive of the present invention include vinyl acetate resin, polyamide resin, polyurethane resin, polyester resin, urea resin, melamine resin, resorcinol resin, phenol resin, epoxy resin, polyimide resin. And an adhesive mainly composed of polybenzimidazole, acrylic (SGA), acrylic acid diester, silicone rubber, and the like. As the alloy, epoxy phenolic, epoxy polysulfide, epoxy nylon, nitrile phenolic, chloroprene phenolic vinyl phenolic, or the like, a resin obtained by modifying the above substances, or a resin in which two or more kinds of the above substances are mixed can be used. In particular, the epoxy resin adhesive is preferable because it cures without liberating by-products and has high shear strength.
本発明の接着剤成分としてエポキシ樹脂を使用する場合、主剤としては、例えば、ビスフェノールA型エポキシ樹脂、ビスフェノールF型エポキシ樹脂、フェノールノボラック型エポキシ樹脂、クレゾールノボラック型エポキシ樹脂、臭素化エポキシ樹脂などのグリシジルエーテル型エポキシ樹脂類、ヘキサヒドロフタル酸グリシジルエステル、ダイマー酸グリシジルエステルなどのグリシジルエステル類、トリグリシジルイソシアヌレート、テトラグリシジルジアミノジフェニルメタンなどのグリシジルアミン類、エポキシ化ポリブタジエン、エポキシ化大豆油などの線状脂肪族エポキサイド類、3,4エポキシ−6メチルシクロヘキシルメチルカルボキシレートなどの脂環族エポキサイド類、あるいはこれらを2種類以上混合したものが使用できる。 When an epoxy resin is used as the adhesive component of the present invention, examples of the main agent include bisphenol A type epoxy resin, bisphenol F type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, brominated epoxy resin and the like. Glycidyl ether type epoxy resins, glycidyl esters such as hexahydrophthalic acid glycidyl ester, dimer acid glycidyl ester, triglycidyl isocyanurate, glycidyl amines such as tetraglycidyl diaminodiphenylmethane, epoxidized polybutadiene, epoxidized soybean oil, etc. Aliphatic epoxides, alicyclic epoxides such as 3,4 epoxy-6 methylcyclohexylmethyl carboxylate, or a mixture of two or more of these You can use.
硬化剤としては、重付加型硬化剤として、例えば、ジエチレントリアミン、メタキシレンジアミン、ジシアンジアミドなどのアミン系硬化剤、無水フタル酸、テトラヒドロメチル無水フタル酸などの酸無水物系硬化剤、その他フェノールノボラック硬化剤やポリメルカプタン硬化剤が使用できる。また、触媒型硬化剤として、例えば第三アミンやルイス酸錯体が使用することができ、これらを2種類以上混合したものが使用できる。
構造用接着剤の場合、実施例で示すような接着強度測定を常温で実施したときに10MPa以上の値を示すものが好ましい。
Curing agents include polyaddition curing agents such as amine curing agents such as diethylenetriamine, metaxylenediamine, and dicyandiamide, acid anhydride curing agents such as phthalic anhydride and tetrahydromethylphthalic anhydride, and other phenol novolak curing agents. Agents and polymercaptan curing agents can be used. Moreover, as a catalyst type hardening | curing agent, a tertiary amine and a Lewis acid complex can be used, for example, and what mixed these 2 or more types can be used.
In the case of structural adhesives, those showing a value of 10 MPa or more when adhesive strength measurement as shown in the examples is carried out at room temperature are preferred.
本明細書中、無機オニウムイオンとは、無機水素化物のプロトン化によって生じたイオンのことであり、例えば、アンモニウムイオン、ヒドロキシルアンモニウムイオン、ヒドラジニウムイオン、ホスホニウムイオン、オキソニウムイオン、スルホニウムイオン、ジアゼニウムイオン、ジアゾニウムイオン等が挙げられ、これらを2種類以上混合したものも使用できる。特に、人体への有害性が比較的低く、接着剤の解体性に優れることから無機オニウムイオンは、窒素の水素化物が好ましく、更にアンモニウムイオンが好ましい。 In the present specification, the inorganic onium ion is an ion generated by protonation of an inorganic hydride, such as ammonium ion, hydroxylammonium ion, hydrazinium ion, phosphonium ion, oxonium ion, sulfonium ion, dia Examples thereof include zenium ions and diazonium ions, and a mixture of two or more of these can also be used. In particular, the inorganic onium ion is preferably a hydride of nitrogen, and more preferably an ammonium ion, because it is relatively low in harmfulness to the human body and has excellent adhesive disassembly.
ハロゲンとは、周期表17族に記されるフッ素、塩素、臭素、ヨウ素のことであり、これらを2種類以上混合したものも使用できる。ハロゲンイオンとしては、特に、接着剤の解体性に優れることからヨウ素が好ましい。 Halogen is fluorine, chlorine, bromine or iodine described in Group 17 of the periodic table, and a mixture of two or more of these can also be used. As the halogen ion, iodine is particularly preferable because it is excellent in the disassembly of the adhesive.
無機オニウムイオンとハロゲンイオンとの化合物の含有量は、有機系接着剤成分100重量部に対して、1重量部以上100重量部以下が好ましい。この範囲であれば、無機オニウムイオンとハロゲンイオンとの化合物の含有量が少なすぎることによる解体性の低下がなく、逆に含有量が多すぎることによる接着剤の著しい粘度上昇はない。より好ましい無機オニウムイオンとハロゲンイオンとの化合物の含有量は、接着剤成分100重量部に対して、2重量部以上50重量部以下であり、さらに好ましくは3重量部以上20重量部以下である。 The content of the compound of inorganic onium ions and halogen ions is preferably 1 part by weight or more and 100 parts by weight or less with respect to 100 parts by weight of the organic adhesive component. If it is this range, there will be no degradation of the dismantling property by too little content of the compound of an inorganic onium ion and a halogen ion, and conversely, there will be no remarkable increase in the viscosity of the adhesive due to too much content. The content of the compound of inorganic onium ions and halogen ions is more preferably 2 parts by weight or more and 50 parts by weight or less, and further preferably 3 parts by weight or more and 20 parts by weight or less with respect to 100 parts by weight of the adhesive component. .
無機オニウムイオンとハロゲンイオンとの化合物の粒径については、一般的に接着剤の厚みが最大でも1mm程度であることから、1mm以下が好ましい。接着剤の塗工作業性が向上し、接着剤成分中における分散性も向上することから、400μm以下が好ましく、100μm以下がより好ましく、10μm以下が特に好ましい。尚、本発明における粒径とは、レーザー回折式粒度分布計を用いて測定したメジアン径をいう。 The particle size of the compound of inorganic onium ions and halogen ions is preferably 1 mm or less since the thickness of the adhesive is generally about 1 mm at the maximum. 400 μm or less is preferable, 100 μm or less is more preferable, and 10 μm or less is particularly preferable because the coating workability of the adhesive is improved and the dispersibility in the adhesive component is also improved. In the present invention, the particle diameter means a median diameter measured using a laser diffraction particle size distribution meter.
本発明においては、接着剤の流動性調整のため、非反応性希釈剤や反応性希釈剤、炭酸カルシウムやタルク、アルミナ等のフィラーを添加することができる。
また、可とう性付与のため、モノエポキサイド、ジエポキサイド、ポリチオールなどの可塑剤や、液状ゴムを添加してもよい。
解体性を向上させるために、熱膨張性黒鉛や熱膨張性樹脂バルーン、アゾジカルボンアミド等の化学発泡剤を添加することもできる。
In the present invention, a non-reactive diluent, a reactive diluent, or a filler such as calcium carbonate, talc, or alumina can be added to adjust the fluidity of the adhesive.
In order to impart flexibility, a plasticizer such as monoepoxide, diepoxide, polythiol, or liquid rubber may be added.
In order to improve dismantling properties, chemical foaming agents such as thermally expandable graphite, thermally expandable resin balloons, and azodicarbonamide can also be added.
接着剤成分と無機オニウムイオンとハロゲンイオンとの化合物、その他流動性調整成分、可とう性付与成分等の混合順は、接着剤の接着強度、解体性等を損なわなければ、どの順序で混合してもよい。また、塗布直前に混合してもよいし、予め一部の成分を混合しておいてもよい。
本発明の接着剤は、液状で用いてもよいし、テープ状で用いるために、フィルム基材に塗布して用いてもよい。
The mixing order of the compound of the adhesive component, inorganic onium ion and halogen ion, other fluidity adjusting component, flexibility imparting component, etc. is the order of mixing as long as the adhesive strength and dismantling properties of the adhesive are not impaired. May be. Moreover, you may mix immediately before application | coating, and may mix one part component previously.
The adhesive of the present invention may be used in liquid form, or may be applied to a film substrate for use in a tape form.
本発明の接着剤は外的刺激によって接着性が低下又は消失するため、該接着剤を用いて接着した接着構造体を容易に解体することが可能となる。
本明細書中、「外的刺激」とは、熱、火等の物理的な刺激をいい、より具体的には、熱風加熱、赤外線照射、高周波加熱、マイクロ波加熱、化学反応熱、摩擦熱等、ガスバーナーなどの火による加熱が挙げられる。本発明の接着剤によって接着された接着構造体に上記外的刺激が与えられると、接着剤の温度が上昇し、接着剤成分自身の凝集力や被着体との接着力が低下するという現象に加え、外的刺激を受けることで、その際、無機オニウムイオンとハロゲンイオンとの化合物が、有機系接着剤の熱分解を促進し、接着力を大きく低減、あるいは、消失させることができる。
Since adhesiveness of the adhesive of the present invention decreases or disappears due to external stimuli, it is possible to easily disassemble an adhesive structure bonded using the adhesive.
In the present specification, “external stimulus” refers to physical stimulus such as heat and fire, and more specifically, hot air heating, infrared irradiation, high frequency heating, microwave heating, heat of chemical reaction, heat of friction. Etc., heating with a fire such as a gas burner. When the external stimulus is applied to the bonded structure bonded by the adhesive of the present invention, the temperature of the adhesive increases, and the cohesive force of the adhesive component itself and the adhesive force with the adherend decrease. In addition, when subjected to an external stimulus, the compound of inorganic onium ions and halogen ions promotes thermal decomposition of the organic adhesive and can greatly reduce or eliminate the adhesive force.
大型の接着された構造体を均一加熱するという点では、電気炉、ガス炉等の内部構造に加熱部を有し、外部が断熱材で構成されたものの内部空間で構造体を加熱する方法がより好ましい。また、解体時の温度としては、金属/FRP接合体、FRP/FRP接合体などは、FRPのマトリックス樹脂の融点以下で短時間での解体を可能とすることは極めて重要な課題である。例えば、複合材料に使用される樹脂PPS(ポリフェニレンサルファイド、融点:280℃)、PEEK(ポリエーテルエーテルケトン、融点:335℃)などの接着構造体の解体においては、リユースを考慮した場合に、樹脂に対して融点以上の温度での加熱を長時間行わないことは樹脂の変質を招かないために重要であり、加熱温度は350℃以下が好ましく、より好ましくは、300℃以下である。 In terms of uniformly heating a large bonded structure, there is a method of heating the structure in the internal space of the internal structure of an electric furnace, gas furnace, etc., where the outside is composed of a heat insulating material. More preferred. As for the temperature at the time of disassembly, it is an extremely important issue that a metal / FRP joined body, an FRP / FRP joined body, etc. can be disassembled in a short time below the melting point of the matrix resin of FRP. For example, when disassembling adhesive structures such as resins PPS (polyphenylene sulfide, melting point: 280 ° C.) and PEEK (polyether ether ketone, melting point: 335 ° C.) used for composite materials, On the other hand, it is important not to perform heating at a temperature equal to or higher than the melting point for a long period of time so as not to cause deterioration of the resin, and the heating temperature is preferably 350 ° C. or lower, more preferably 300 ° C. or lower.
加熱解体時の昇温速度については、被接着体の熱劣化を抑制すること、また、高い解体性を付与する場合があることから、高い昇温速度で接着剤を加熱することが好ましく、具体的には5℃/min以上、より好ましくは10℃/min以上の昇温速度で昇温することが好ましい。
また、被接着体のリサイクル等を考慮すると、リサイクル等したい側の被接着体界面で剥離させることが望ましい。このため、リサイクル等したい被接着体側から加熱することで、解体面を選択することができる。
本発明の接着剤の使用箇所は、特に制限されるものではないが、リサイクル、リユース、リワーク用途に使用することが可能であり、金属−FRPや、金属−ガラスのような異材質の接着に好適に用いることができる。また、異種の金属−金属、FRP−FRPの接着に用いることも可能である。
Regarding the heating rate at the time of heating demolition, it is preferable to heat the adhesive at a high heating rate because it suppresses thermal degradation of the adherend and may give high dismantling properties. Specifically, it is preferable to raise the temperature at a rate of temperature increase of 5 ° C./min or more, more preferably 10 ° C./min or more.
In consideration of recycling of the adherend, etc., it is desirable to peel at the interface of the adherend to be recycled. For this reason, a disassembly surface can be selected by heating from the adherend side to be recycled.
The location of use of the adhesive of the present invention is not particularly limited, but can be used for recycling, reuse, and rework applications. For bonding of different materials such as metal-FRP and metal-glass. It can be used suitably. It can also be used for bonding different metals-metals, FRP-FRP.
以下、実施例で本発明を具体的に説明するが、本発明はこれらの実施例に限定されるものではない。
構造用接着剤として、広く用いられるエポキシ樹脂系接着剤を用いた。エポキシ樹脂系接着剤は、主剤としてビスフェノールF型エポキシ(株式会社ADEKA社製、商品名アデカレジンEP−4901)、硬化剤として、変性脂肪族ポリアミン(株式会社ADEKA社製、商品名アデカハードナーEH−463)を使用した。
無機オニウムイオンとハロゲンイオンとの化合物として、ヨウ化アンモニウム(和光純薬工業株式会社製)、塩化アンモニウム(和光純薬工業株式会社製)を使用した。
各実施例、各比較例について、以下の表1に示す組成で、接着接合体の作成、引張剪断試験、加熱解体試験を以下の方法で行った。
EXAMPLES Hereinafter, although an Example demonstrates this invention concretely, this invention is not limited to these Examples.
A widely used epoxy resin adhesive was used as the structural adhesive. The epoxy resin-based adhesive is a bisphenol F type epoxy (manufactured by ADEKA Corporation, trade name Adeka Resin EP-4901) as a main agent, and a modified aliphatic polyamine (manufactured by ADEKA Corporation, trade name Adeka Hardener EH-463) as a curing agent. )It was used.
As a compound of inorganic onium ions and halogen ions, ammonium iodide (Wako Pure Chemical Industries, Ltd.) and ammonium chloride (Wako Pure Chemical Industries, Ltd.) were used.
About each Example and each comparative example, creation of an adhesive joined body, a tensile shear test, and a heating dismantling test were performed by the following methods with the compositions shown in Table 1 below.
<接着接合体の作製>
以下の表1に示す各接着剤組成に従い、主剤、無機オニウムイオンとハロゲンイオンとの化合物、硬化剤の順に十分混合し、接着剤を作製した。被接着体は、幅25mm、長さ100mm、厚さ1.6mmの金属板(SUS304製)を用い、ラップ長は12.5mmとした。接着面は、紫外線オゾン処理による表面処理を行った。接着面に、作成した接着剤を塗布して張り合わせ、接着接合部をクリップで止め、25℃の恒温槽中で24時間保持した(プレキュア)。その後、120℃の電気炉で1時間保持し、硬化させた(ポストキュア)。
<Preparation of bonded assembly>
According to each adhesive composition shown in Table 1 below, the main agent, a compound of inorganic onium ions and halogen ions, and a curing agent were sufficiently mixed in this order to prepare an adhesive. As the adherend, a metal plate (made of SUS304) having a width of 25 mm, a length of 100 mm, and a thickness of 1.6 mm was used, and the wrap length was 12.5 mm. The adhesion surface was subjected to surface treatment by ultraviolet ozone treatment. The prepared adhesive was applied to the adhesive surface and pasted together, and the adhesive joint was stopped with a clip and held in a thermostatic bath at 25 ° C. for 24 hours (precure). Thereafter, it was held in an electric furnace at 120 ° C. for 1 hour and cured (post cure).
<引張剪断試験>
上記方法で得られた接着接合体を25℃まで冷却後、株式会社島津製作所製オートグラフ(型式AGS−J、ロードセル1トン用)を用いて、引張モード、変位速度5mm/minで試験片が破壊するまでの最大荷重を測定した。最大荷重を接着接合部の面積で除して、引張剪断接着強さを算出した。5試験体について測定を行い、その平均値を算出した。測定結果を以下の表1に示す。
<Tensile shear test>
After the bonded assembly obtained by the above method is cooled to 25 ° C., a test piece is obtained at a tensile mode and a displacement speed of 5 mm / min using an autograph (model AGS-J, for 1 ton load cell) manufactured by Shimadzu Corporation. The maximum load until failure was measured. The tensile shear bond strength was calculated by dividing the maximum load by the area of the adhesive joint. Measurements were made on five specimens, and the average value was calculated. The measurement results are shown in Table 1 below.
<加熱解体試験>
上記方法で得られた接着接合体を25℃まで冷却後、剥離試験時の加熱は、電気炉を用いて実施した。270℃の加熱炉に試験片を入れ、30分間加熱し、加熱により接着接合部が解体するか確認を行った。解体していなかった場合には、上記と同一の試験条件で引張剪断強度を得た。結果を以下の表1に示す。
<Heating disassembly test>
After the bonded assembly obtained by the above method was cooled to 25 ° C., the heating during the peeling test was carried out using an electric furnace. The test piece was put in a heating furnace at 270 ° C., heated for 30 minutes, and it was confirmed whether the bonded joint was disassembled by heating. When not dismantled, tensile shear strength was obtained under the same test conditions as above. The results are shown in Table 1 below.
実施例1、実施例2の解体性接着剤は、無機オニウムイオンとハロゲンイオンとの化合物の潮解性がないため、通常の大気雰囲気化で問題なく接着剤の混合、貼り付け作業を行うことができた。また、無機オニウムイオンとハロゲンイオンとの化合物と硬化剤との反応性もなく、発泡等の強度低下につながるような事象も観られなかった。 Since the decomposable adhesives of Example 1 and Example 2 do not have the deliquescent properties of the compound of inorganic onium ions and halogen ions, the adhesives can be mixed and pasted without problems in normal atmospheric conditions. did it. In addition, there was no reactivity between the compound of inorganic onium ions and halogen ions and the curing agent, and no event that would lead to a decrease in strength such as foaming was observed.
実施例1の条件では、10MPa以上の引張剪断強度を有するが270℃30分の加熱により、1MPa程度まで接着強度を低下させることが分かった。実施例2の条件では、10MPa以上の引張剪断強度を有するが、270℃の加熱中に接着強度が消失し、接着接合部が解体した。しかしながら、無機オニウムイオンとハロゲンイオンとの化合物を含まない比較例1の接着剤は、10MPa以上の接着強度を有するものの、270℃30分の加熱後も引張剪断強度の低下が観られなかった。 Under the conditions of Example 1, it has a tensile shear strength of 10 MPa or more, but it was found that the adhesive strength was reduced to about 1 MPa by heating at 270 ° C. for 30 minutes. Under the conditions of Example 2, it had a tensile shear strength of 10 MPa or more, but the adhesive strength disappeared during heating at 270 ° C., and the adhesive joint was disassembled. However, although the adhesive of Comparative Example 1 containing no compound of inorganic onium ions and halogen ions has an adhesive strength of 10 MPa or more, no decrease in tensile shear strength was observed after heating at 270 ° C. for 30 minutes.
本発明の解体性接着剤を使用すれば高強度の接着剤を容易に解体することができる。従って、本発明の接着剤は、リサイクル、リユース、リワーク用途に有用であり、金属−FRPや、金属−ガラスのような異材質の接着に好適に用いることができる。 By using the disassembling adhesive of the present invention, a high-strength adhesive can be easily disassembled. Therefore, the adhesive of the present invention is useful for recycling, reuse, and rework applications, and can be suitably used for bonding different materials such as metal-FRP and metal-glass.
Claims (5)
Priority Applications (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| JP2014076467A JP6348317B2 (en) | 2014-04-02 | 2014-04-02 | Decomposable adhesive composition |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| JP2014076467A JP6348317B2 (en) | 2014-04-02 | 2014-04-02 | Decomposable adhesive composition |
Publications (2)
| Publication Number | Publication Date |
|---|---|
| JP2015196793A JP2015196793A (en) | 2015-11-09 |
| JP6348317B2 true JP6348317B2 (en) | 2018-06-27 |
Family
ID=54546703
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| JP2014076467A Expired - Fee Related JP6348317B2 (en) | 2014-04-02 | 2014-04-02 | Decomposable adhesive composition |
Country Status (1)
| Country | Link |
|---|---|
| JP (1) | JP6348317B2 (en) |
Families Citing this family (8)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JP6974823B2 (en) * | 2016-05-31 | 2021-12-01 | 国立大学法人神戸大学 | Adhesive composition for microwave dismantling and method of dismantling adhesive |
| CN107057639A (en) * | 2017-06-05 | 2017-08-18 | 冯新平 | A kind of high temperature resistant regeneration bonded adhesives and its preparation technology |
| JP6986479B2 (en) * | 2018-04-04 | 2021-12-22 | 旭化成株式会社 | Demolition adhesive composition |
| EP3835383B1 (en) | 2019-12-13 | 2023-04-12 | Henkel AG & Co. KGaA | One component (1k) curable adhesive composition |
| WO2021251099A1 (en) * | 2020-06-12 | 2021-12-16 | 国立大学法人九州大学 | Easily disintegrable adhesive material, article and disintegration method |
| EP3943564B1 (en) * | 2020-07-21 | 2024-07-17 | Henkel AG & Co. KGaA | Room temperature stable, electrically conductive 1k epoxy formulation |
| JP2024103857A (en) | 2023-01-23 | 2024-08-02 | 信越化学工業株式会社 | Addition-curable silicone composition, silicone cured product, bonded member, and method for dismantling bonded members |
| EP4682209A1 (en) * | 2023-03-15 | 2026-01-21 | Sumitomo Bakelite Co.Ltd. | Easily degradable resin composition, structure provided with cured product of easily degradable resin composition, method for disassembling structure, and method for recycling material forming structure |
Family Cites Families (9)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JP4297644B2 (en) * | 2002-02-28 | 2009-07-15 | コニシ株式会社 | Water-based adhesive composition |
| JP2005325224A (en) * | 2004-05-14 | 2005-11-24 | Matsushita Electric Ind Co Ltd | Adhesive composition for adsorbing carbon dioxide and method of using the same |
| JP4775622B2 (en) * | 2004-10-14 | 2011-09-21 | Dic株式会社 | Epoxy resin composition for easy-dismantling adhesive, easy-dismantling adhesive, and dismantling method using the same |
| JP2006225544A (en) * | 2005-02-18 | 2006-08-31 | Nagase Chemtex Corp | Epoxy resin adhesive |
| JP2008024851A (en) * | 2006-07-21 | 2008-02-07 | Mitsui Chemicals Inc | Biodegradable composition, and molded article and use of the same |
| JP2008024849A (en) * | 2006-07-21 | 2008-02-07 | Mitsui Chemicals Inc | Water disintegrable composition containing water environment-responding type polymer having biodegradability, and water disintegrable molded article |
| CN101743288B (en) * | 2007-07-19 | 2012-07-18 | 旭化成化学株式会社 | Detachable adhesive containing reaction product of oxidizing agent and amine compound |
| JP5536520B2 (en) * | 2009-04-20 | 2014-07-02 | 電気化学工業株式会社 | Disassembly method of adhesive member |
| JP2011042705A (en) * | 2009-08-19 | 2011-03-03 | Asahi Kasei Chemicals Corp | Dismantling adhesive containing halogen-based dismantling component |
-
2014
- 2014-04-02 JP JP2014076467A patent/JP6348317B2/en not_active Expired - Fee Related
Also Published As
| Publication number | Publication date |
|---|---|
| JP2015196793A (en) | 2015-11-09 |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| JP2015196793A (en) | Decomposable adhesive composition | |
| CN102884130B (en) | Low toxicity one-component epoxy resin composition | |
| CN103228696A (en) | One component epoxy resin composition | |
| JP2011111570A (en) | One-pack epoxy resin composition and application thereof | |
| WO2007125925A1 (en) | Epoxy resin composition for fiber-reinforced composite material | |
| CN111971362A (en) | Epoxy resin adhesive composition | |
| US11988304B2 (en) | Tubular elements with adhesive joint, method of joining tubular elements thereof | |
| JP3906634B2 (en) | One-part epoxy resin composition | |
| CN106062027A (en) | Method for curing resin composition | |
| JP5143135B2 (en) | Dismantling adhesive containing reaction product of oxidizing agent and amine compound | |
| JP2016065164A (en) | Heat-expandable adhesive sheet and method for bonding components | |
| JP2003160641A (en) | Liquid amine composition, two-pack repair / reinforcing agent, and method for repairing / reinforcing concrete structure using the same | |
| JP6346770B2 (en) | Decomposable adhesive composition | |
| JP2009114276A (en) | Decomposable adhesive composition | |
| US11279795B2 (en) | Curable composition | |
| JP2011042705A (en) | Dismantling adhesive containing halogen-based dismantling component | |
| CN114829445B (en) | Gap Filling Adhesive | |
| JP7539886B2 (en) | Flame retardant epoxy-based compositions and methods of using same | |
| JP4567377B2 (en) | Latent curing agent and composition | |
| KR102080030B1 (en) | Thermally Conductive Adhesive Composition | |
| JPWO2009075273A1 (en) | Manufacturing method of liquid crystal display device | |
| JP6385116B2 (en) | Heat-curing epoxy resin curing agent and one-component heat-curing epoxy resin composition containing the same | |
| JP6690809B2 (en) | Epoxy resin adhesive | |
| JP2024055044A (en) | Dismantlable adhesive composition and method for producing same | |
| JP2019182948A (en) | Decomposable adhesive composition |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| A711 | Notification of change in applicant |
Free format text: JAPANESE INTERMEDIATE CODE: A712 Effective date: 20160404 |
|
| A621 | Written request for application examination |
Free format text: JAPANESE INTERMEDIATE CODE: A621 Effective date: 20170202 |
|
| A977 | Report on retrieval |
Free format text: JAPANESE INTERMEDIATE CODE: A971007 Effective date: 20171124 |
|
| A131 | Notification of reasons for refusal |
Free format text: JAPANESE INTERMEDIATE CODE: A131 Effective date: 20171212 |
|
| A521 | Request for written amendment filed |
Free format text: JAPANESE INTERMEDIATE CODE: A523 Effective date: 20180126 |
|
| TRDD | Decision of grant or rejection written | ||
| A01 | Written decision to grant a patent or to grant a registration (utility model) |
Free format text: JAPANESE INTERMEDIATE CODE: A01 Effective date: 20180515 |
|
| A61 | First payment of annual fees (during grant procedure) |
Free format text: JAPANESE INTERMEDIATE CODE: A61 Effective date: 20180531 |
|
| R150 | Certificate of patent or registration of utility model |
Ref document number: 6348317 Country of ref document: JP Free format text: JAPANESE INTERMEDIATE CODE: R150 |
|
| S531 | Written request for registration of change of domicile |
Free format text: JAPANESE INTERMEDIATE CODE: R313531 |
|
| R350 | Written notification of registration of transfer |
Free format text: JAPANESE INTERMEDIATE CODE: R350 |
|
| LAPS | Cancellation because of no payment of annual fees |
